Pengembangan Bahan Ajar Menulis Teks Prosedur Bermuatan Kearifan Lokal Mandailing untuk Siswa Kelas XI SMK Kesehatan Imelda Ritonga - Uci Rahmadhani; Muharrina Harahap; Fitriani Lubis (Varied Knowledge Journal, 2026)
This study aims to develop instructional materials for writing procedural texts based on Mandailing local wisdom for eleventh-grade students at Imelda Ritonga Health Vocational High School and to examine their feasibility, practicality, and effectiveness in Indonesian language learning. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. Data were collected through observations, interviews, questionnaires, expert validation, and learning achievement tests. The research participants included a subject-matter expert, an instructional design expert, an Indonesian language teacher, and eleventh-grade students. The product developed was a procedural text writing module that integrates Mandailing local wisdom through the context of preparing the traditional food Itak Poul-Poul. The validation results indicated that the instructional materials were categorized as highly feasible, with an average score of 91.5%. The practicality test showed very positive responses from both teachers and students, with an average percentage of 92%. Furthermore, the effectiveness test revealed an improvement in students’ learning outcomes, as demonstrated by an increase in the average score from 68.40 on the pretest to 85.70 on the posttest. These findings indicate that the developed instructional materials can enhance students’ procedural text writing skills while introducing local cultural values. Therefore, the instructional materials are considered valid, practical, and effective, and they have the potential to support the preservation of local culture through education.